THE EFFECT OF PERFORMANCE APPRAISAL AND BONUS PROVISION ON EEMPLOYEE JOB STATISFACTION DURING THE COVID – 19 PANDEMIC CASE STUDY AT PT SUMBER MEGA JAYA COMPANY - Dana Yulianto (Jurnal Cakrawala Ilmiah, 2023)
The research that has been carried out is related to how performance appraisals and bonus payments can affect employee job satisfaction at PT. Sumber Mega Jaya. The purpose of carrying out this research is to determine whether performance appraisal has an influence on job satisfaction and to find out whether bonus payments have an influence on job satisfaction. This study used respondents, namely all employees of PT. Sumber Mega Jaya totaling 76 people consisting of permanent employees and contract employees. The method of data collection used is by distributing questionnaires. Data analysis techniques used in this study using quantitative analysis techniques used for t-test, F-test and multiple regression analysis. Data analysis was carried out using the SPSS 25.0 program. The results in the study obtained that the employee performance appraisal variable has a positive and significant effect on the employee job satisfaction variable, with a β value of 0.507 or 50.7%, while the remaining 49.3% can be influenced by other variables that are not considered in this study. The bonus distribution variable in this study has a positive and significant effect on the job satisfaction variable with a β value of 0.237 or 23.7%, and the remaining 76.3% can be influenced by other variables that are not considered in this study.